2020
DOI: 10.3390/microorganisms8030375
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution of Acinetobacter baumannii in Germany—A Comprehensive Systematic Review of Studies on Resistance Development in Humans (2000–2018)

Abstract: Acinetobacter (A.) baumannii has gained global notoriety as a significant nosocomial pathogen because it is frequently associated with multi-drug resistance and hospital-based outbreaks. There is a substantial difference in the incidence of A. baumannii infections between different countries and within Germany. However, its continuous spread within Germany is a matter of concern. A systematic literature search and analysis of the literature published between 2000 and 2018 on A. baumannii in humans was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 77 publications
(152 reference statements)
2
10
0
Order By: Relevance
“…The oxacillinase bla OXA-23 was identified for the first time in A. baumannii strains isolated from the United Kingdom in 1993. Later, it has been found and linked to the dissemination of carbapenem-resistant in A. baumannii worldwide [40] and is one of the most dominant resistance genes described in A. baumannii in Germany last decade [5]. The ADC beta-lactamases are cephalosporinase with extended-spectrum resistance to cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxacillinase bla OXA-23 was identified for the first time in A. baumannii strains isolated from the United Kingdom in 1993. Later, it has been found and linked to the dissemination of carbapenem-resistant in A. baumannii worldwide [40] and is one of the most dominant resistance genes described in A. baumannii in Germany last decade [5]. The ADC beta-lactamases are cephalosporinase with extended-spectrum resistance to cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered one of the critical pathogens that need developing new antibiotics [3,4]. In Germany, A. baumannii is a ubiquitous pathogen, and several communities and hospital-based outbreaks were reported in 13 out of 16 federal states [5]. Among other sources, the pathogen was also isolated from companion animals [6] and found in dried milk samples [7].…”
Section: Introductionmentioning
confidence: 99%
“…So far, genetic typing of Polish strains of A. baumannii has not been carried out using the Oxford scheme. Among the A. baumannii strains isolated in Europe, the following above-mentioned sequence types have been described: ST195 in Croatia, ST208 in Bulgaria and Greece, ST348 in Germany and ST425 in Greece [ 31 , 32 , 33 , 34 , 35 ]. Carbapenem-resistant A. baumannii ST195 and ST208 are widespread in the world, and are dominant mainly in the Far East, e.g., in China [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter baumannii is a serious and emerging pathogen, causing nosocomial infections in humans and animals in Germany [2,5,7,8]. Accurate identification and differentiation of Acinetobacter at the species level is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-drug resistant (MDR) A. baumannii strains are the cause of both hospital-and community-acquired infections worldwide [1]. In Germany, several outbreaks have occurred among hospitalized patients [2] and in veterinary clinics [3][4][5], and a recent study identified A. baumannii in dried milk [6,7]. The impact of A. baumannii in veterinary medicine and food chains is not well understood [8].…”
Section: Introductionmentioning
confidence: 99%